2011
DOI: 10.5851/kosfa.2011.31.6.799
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Aging Period Prior to Freezing on Meat Quality of Hanwoo Muscle (Longissimus dorsi)

Abstract: This study was conducted to evaluate the effect of the aging period prior to freezing on the meat quality of Hanwoo longissimus dorsi (LD) muscle. Three different combinations of aging and freezing periods (0/90, 20/70, and 40/50) were examined using LD muscle at 24 h postmortem under an identical storage time of 90 d. The pH and lightness slightly increased with increasing aging period. However, there were no significant (p>0.05) differences in redness and yellowness. The solitary freezing treatment (0/90) ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 26 publications
(26 reference statements)
0
3
0
Order By: Relevance
“…The aged first then-frozen/thawed beef samples (A3F2) had the numerically lowest purge loss among other frozen/thawed beef samples. Previous studies have suggested that aging prior to freezing could improve WHC of frozen/thawed meat, particularly thaw loss [2,3,16,17]. Farouk et al [16] explained this phenomenon as “sponge effect” that aging prior to freezing decreased purge/thaw loss of meat samples through the structural disintegration by proteolysis and subsequent disruption of drip channel, which, in turn, entraps the free water in muscle tissue.…”
Section: Resultsmentioning
confidence: 99%
“…The aged first then-frozen/thawed beef samples (A3F2) had the numerically lowest purge loss among other frozen/thawed beef samples. Previous studies have suggested that aging prior to freezing could improve WHC of frozen/thawed meat, particularly thaw loss [2,3,16,17]. Farouk et al [16] explained this phenomenon as “sponge effect” that aging prior to freezing decreased purge/thaw loss of meat samples through the structural disintegration by proteolysis and subsequent disruption of drip channel, which, in turn, entraps the free water in muscle tissue.…”
Section: Resultsmentioning
confidence: 99%
“…However, it is important to highlight that both CHF and CH meat were scored positively (at least ‘like slightly’). It has been reported that ageing prior to freezing may be an effective procedure to improve beef tenderness and sensorial properties 40,42 . The flavor of VPAM + CH treatment was the least preferred by consumers.…”
Section: Discussionmentioning
confidence: 98%
“…It has been reported that ageing prior to freezing may be an effective procedure to improve beef tenderness and sensorial properties. 40,42 The flavor of VPAM + CH treatment was the least preferred by consumers. We hypothesized that meat stored for 120 d under CH condition and packaged with VPAM bags that had greater OTR and MVTR would promote the slight appearance of some off flavors having a small negative impact on consumers' preferences.…”
Section: Discussionmentioning
confidence: 99%